Physiology of sport and exercise - Kenney, W. L.; Wilmore, J. H.; Costill, D. L. (Human Kinetics, 2020)
Book Physiology of Sport and Exercise, Seventh Edition With Web Study Guide, continues its legacy as a top physiology textbook and favorite of instructors and students alike. Combining research with extensive visual aids, this resource offers a simple way for students to develop an understanding of the body`s abilities to perform various types and intensities of exercise and sport, to adapt to stressful situations, and to improve its physiological capacities.